Proceedings of IEEE Sensors, 2004.
DOI: 10.1109/icsens.2004.1426208
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic bistable micro-actuator with integrated permanent magnets

Abstract: A new magnetic micro-actuator with integrated permanent magnets has been developed. The design of this device with a levitating mobile magnet is a real innovation and is patented. The structure was modeled using analytical and numerical calculations. Furthermore, the fabrication feasibility, using collective micro-technology processes, has recently been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 1 publication
(1 reference statement)
0
24
0
Order By: Relevance
“…As a result, a new generation of micro-sensors and actuators based on levitation have been demonstrated, covering a wide range of applications, e.g., as microinertial sensors [1]- [4], frictionless micro-bearings [5], [6], bistable switches [7], micro-accelerator [8], linear-micro-actuator [9], and nano-force sensor [10]. We will generally refer to all these devices as contactless suspensions (CS).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a new generation of micro-sensors and actuators based on levitation have been demonstrated, covering a wide range of applications, e.g., as microinertial sensors [1]- [4], frictionless micro-bearings [5], [6], bistable switches [7], micro-accelerator [8], linear-micro-actuator [9], and nano-force sensor [10]. We will generally refer to all these devices as contactless suspensions (CS).…”
Section: Introductionmentioning
confidence: 99%
“…16 The integration of high performance NdFeB into a modified version of this micro-switch, by the consecutive application of the processing steps developed in this work (figure 6), is presently being studied. 17 Note that in this process flow the wet etching step is not used to define the final size of the magnet but as a coarse patterning step prior to CMP.…”
Section: Discussionmentioning
confidence: 99%
“…The permanent magnet of 1 mm 3 volume was lifted up to 200 µm by generating a levitation force of 20 µN. Dieppedale et al developed and demonstrated a prototype of MLMA, in which a levitating mobile magnet of 5×40×100 µm 3 volume was used [43]. The prototype employed a bistable actuation principle and was used as a micro-switch.…”
Section: Magnetic Levitation Micro-actuatorsmentioning
confidence: 99%